Dataset of differentially regulated proteins in HUVECs challenged with wild type and UGM1 mutant Aspergillus fumigatus strains - Gabriela Westerlund Peixoto Neves; Nathália Curty; Paula Helena Kubitschek-Barreira; Thierry Fontaine; Gustavo Henrique Martins Ferreira Souza; Marcel Lyra Cunha; Gustavo H. Goldman; Anne Beauvais; Jean-Paul Latgé; Leila M. Lopes-Bezerra (Data in Brief, 2016)
Invasive aspergillosis is the primary opportunistic invasive fungal infection described in neutropenic hematologic patients, caused by the angioinvasive pathogen Aspergillus fumigatus. The molecular mechanisms associated with A. fumigatus infection in the vascular endothelium are poorly understood. In this context, we used a high-throughput proteomic approach to unveil the proteins modulated in HUVECs after interaction with a wild type strain and the UGM1 mutant (Δugm1) of A. fumigatus. The proteomic analysis was also performed in HUVECs challenged with a galactosaminogalactan (GAG) purified from A. fumigatus cell wall. The dataset presented here correspond to all proteins identified that fit a 2-fold change criteria (log 2 ratio ≥ 1 or ≤ −1), disregarding the statistical validation cut off, in order to supplement the research article entitled “Modifications to the composition of the hyphal outer layer of Aspergillus fumigatus modulates the HUVEC proteins associated with inflammatory and stress responses” (G.W.P. Neves, N.A. Curty, P.H. Kubitschek-Barreira, T. Fontaine, G.H.M.F. Souza, M. Lyra Cunha, G.H. Goldman, A. Beauvais, J.P. Latgé, L.M. Lopes-Bezerra, 2016) [1]. The mass spectrometry proteomic data have been deposited in the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PRIDE: PXD002823.